2017
DOI: 10.1088/2053-1583/aa61e0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering pn junctions and bandgap tuning of InSe nanolayers by controlled oxidation

Abstract: Exploitation of two-dimensional (2D) van der Waals (vdW) crystals can be hindered by the deterioration of the crystal surface over time due to oxidation. On the other hand, the existence of a stable oxide at room temperature can offer prospects for several applications. Here we report on the chemical reactivity of γ-InSe, a recent addition to the family of 2D vdW crystals. We demonstrate that, unlike other 2D materials, InSe nanolayers can be chemically stable under ambient conditions. However, both thermal-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 39 publications
5
67
0
1
Order By: Relevance
“…. 32 It is expected that these defective states act as trapping and scattering centers for conducting carriers and decrease their electronic mobility.…”
Section: Computational Detailsmentioning
confidence: 99%
“…. 32 It is expected that these defective states act as trapping and scattering centers for conducting carriers and decrease their electronic mobility.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Balakrishnan et al controllably oxidized the surface of InSe nanolayers by photo-annealing and thermal-annealing in air, and obtained InSe/In 2 O 3 heterostructures as p-n junctions with tunable band gap. 30 Beechem et al and Del Pozo-Zamudio et al showed that oxidation of ultrathin GaSe and InSe films lead to the reduction of photoluminescence. 31,32 However, the structures, physical, and chemical properties of the modified MX sheets are still unclear and await explorations.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally perfect InSe crystals are characterized by higher values of electron mobility (>10 3 cm 2 V −1 s −1 at Т = 300 K) as compared to other 2D materials. They are also more resistant with respect to environment influence (molecules of H 2 O and O 2 ) . Various van der Waals heterostructures based on this material have high‐quality interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…They are also more resistant with respect to environment influence (molecules of H 2 O and O 2 ) . Various van der Waals heterostructures based on this material have high‐quality interfaces . Intense researchеs of 2D materials resulted in the creation of a new class of structures that have “ionotronic” characteristics .…”
Section: Introductionmentioning
confidence: 99%